E-Resource Management Model in Indonesian Libraries: A Case Study on BRIN Library - Rahma, Nurida Maulidia; Pramudyo, Gani Nur (Program Studi Ilmu Perpustakaan UIN Alauddin, 2023)
The National Research and Innovation Agency of Indonesia (BRIN) is aware of the changes in the information/reference-seeking behavior of BRIN researchers, where many refer to electronic journals as references for their scientific work. Therefore, BRIN has implemented a new policy in procuring its library collections, namely by no longer carrying out procurement in printed form but rather digital/electronic. This research aims to determine the readiness of the BRIN library in e-resource services so that it can be used as material for evaluation and improvement of the BRIN library. This research method uses a qualitative approach with a case study type. Data collection was carried out using semi-structured interviews, observation, and documentation. Data analysis uses the Strauss and Corbin analysis models, starting from open coding, axial coding, and selective coding. Triangulation of sources and techniques is used to maintain the validity of the data provided. The results of this research can be used as a reference and framework model that can be applied in libraries to manage their e-resources well. Future research can test whether this model can effectively manage e-resources.